Russian language in the educational environment of the Republic of Tajikistan - Khalimzoda, Ziyovidin Amirkhudzha (Филология: научные исследования, 2024)
This article is devoted to the issue of studying the Russian language in the field of education of the Republic of Tajikistan, as well as in secondary schools, where education is conducted entirely in the Tajik language, taking into account the increased efficiency of mastering the Russian language. The question is raised about the need to take into account the native language of students when teaching Russian to Tajik schoolchildren. The grammatical categories of number, gender and case of the noun in the analyzed languages are analyzed, and the similarities and differences of the concepts under consideration are determined. Particular attention is paid to the issues of teaching the Russian language due to the fact that in the linguistic conditions of Tajikistan, in the absence of a natural Russian-speaking environment, the education system bears the main burden in learning and preserving the language. Today, among the various directions of socio-economic development of Tajikistan, special attention is paid to the issue of learning languages, especially Russian. Indeed, every year in our country the number of people interested in learning Russian and other languages of the East and West is increasing, and the number of young people interested in learning several languages is increasing every year. In the Republic of Tajikistan (RT), the educational process in the Russian language in secondary schools is built on a new program.Today, among the various directions of socio-economic development of Tajikistan, special attention is paid to the issue of learning languages, especially Russian. Indeed, every year in our country the number of people interested in learning Russian and other languages of the East and West is increasing, and the number of young people interested in learning several languages is increasing every year.